Knowledge Regarding Earthquake Preparedness Among the People of Biratnagar Sub-Metropolis of Eastern Nepal - Pokharel, Alpha; Parajuli, P; Parajuli, S (Birat Journal of Health Sciences, 2017)
IntroductionEarthquake preparedness is necessary strategy and action that is done before an earthquake happens in order to decrease mortality and morbidity. Earthquake in Nepal killed more than 8000 people in 2015. Increased number of deaths were mainly considered due to lack of earthquake preparedness and necessary safety measures.ObjectivesThe aim of this study was to assess the knowledge regarding earthquake preparedness and to ﬁnd out relationship between the level of knowledge and with their selected socio-demographic variables.MethodologyA cross sectional study was conducted among the people residing in ward number 11 and 18 of Biratnagar sub-metropolis from 1st July to 1st October 2015. Wards were selected through simple random sampling and 110 participants were selected through convenient sampling. Each participant had completed an interviewer-administered questionnaire. Descriptive and inferential statistics was applied for data analysis.ResultAmong 110 participants, 51.8% had knowledge score between 51% to 75%, 24.6% had knowledge score below 50% and only 23.6% had knowledge score above 75%. This research showed that there was signiﬁcant relationship between knowledge and age, marital status, educational status, occupation and monthly income. Participants from 20 to 39 year had more knowledge score than participants from 40 to 60 years. The higher the educational status; more was the knowledge score. Unmarried participants had more knowledge score than married participants and business holders had more knowledge score than other occupation category.ConclusionEarthquake preparedness knowledge among participants was inadequate. Therefore, educational intervention program regarding this is required in these areas. Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, page: 201-205